Perlindungan Hukum Terhadap Adat Pamali Kekerasan Dalam Rumah Tangga - Wadjo, Hadibah Zachra; Wessy, Yeheskel; Noya, Stelvia Wemly; Ririhena, Michael (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Domestic violence is prohibited because it has an impact from the private sphere to the public domain. It is inevitable, that the problem of domestic violence for some people is still seen as a disgrace in the family, so it is not worthy of being known by society in the social environment.Purposes of Devotion: To increase public awareness about the Importance of Legal Protection Against Customary "Pamali" Domestic Violence in Tutuwaru Village, Leti Island District, Southwest Maluku Regency. Method of Devotion: Conducted face-to-face through the lecture method by the speaker, then providing opportunities for participants to discuss and question and answer related to Legal Protection of Indigenous Pamali Domestic Violence.Results of the Devotion: The indigenous people of Tutuwaru Village further increase legal awareness for the creation of harmonious and prosperous families in the social environment of indigenous people, due to the lack of acts of domestic violence so that indigenous people with the village government together with the entire community can suppress the absence of domestic violence in the future.